Rancang Bangun Sistem Pembelajaran Tenses Berbasis Macromedia Flash 8 - Afis Pratama; Raden Arum SP (Universitas Lampung, 2013)
Abstract In this study, the tenses learning system will be designed by using Macromedia Flash 8 software. This system aims to enhance the enthusiasm of learning from students in an effort to understand the English tenses. In this learning system, there are 16 tenses material, some exercises, and 3 kinds of tests are presented in interesting way. This system can also be used by teacher to test the ability of the students in understanding tenses. Teacher who have role as the admin can also use the program interface to update the problems that have been there before and will be stored in the database PHP.Keywords: learning system, tenses, Macromedia Flash 8, PHP.